Short Stature as a Major Manifestation of Celiac Disease in Children 1-14 years of age at Shaikh Zayed Hospital Lahore - Maria Javed, Lubna Riaz, Asfand Tariq, Azka Perveen, Amna Basharat Ali, Aimen Javaid (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To find the frequency of asymptomatic celiac disease in children with proportionately short stature. Methodology: This prospective study was carried out at the Department of Paediatrics, Shaikh Zayed Hospital, Lahore. A total of 151 cases of proportionate short stature were selected according to selection criteria and informed consent. Their history, examination, and detailed demographics were recorded. They were tested for anti-Tissue Transglutaminase2 IgA antibody levels, and the results were interpreted. Results: Fifty (33.1%) were males and 101(66.9%) were females, with a mean age of 7.7±3.3 and a mean height of 106.9±17.0. Anti-TG2 IgA levels were positive in 15 (9.9%) patients and negative in 136(90.1%) patients. The frequency of asymptomatic celiac disease among proportionately short statures is 9.9%. Conclusion: The frequency of 9.9% cases of asymptomatic CD among children with pathologically proportionately short stature. Keywords: Extra-intestinal manifestations, Asymptomatic celiac disease, Short stature, Children